Innovations in Globalized Regulation : Opportunities and Challenges - Levy, Brian (2012)
This paper lays out a comparative framework for assessing the potential, limitations and challenges of a variety of emerging institutional innovations in globalized regulation. The framework highlights two dimensions of effectiveness -- the comprehensiveness of coverage, and the credibility of the regulatory regime. Performance in relation to these two dimensions is assessed for three distinctive approaches to globalized regulation: i) Government-centric approaches, including treaties, extra-territorial regulation and government networks -- seven examples are assessed in the paper. ii) Civil regulation, including both joint initiatives by private firms and civil society, and wholly private self-regulatory approaches -- with eight examples assessed. iii) Hybrid approaches, involving multiple governmental and non-governmental stakeholders -- with three examples assessed. Overall, the assessment points to an abundance of innovation -- but a seeming failure of the many innovations to deliver more than, at best, partial successes in meeting the credibility and comprehensiveness criteria for effectiveness. The paper concludes by suggesting ways in which the distinct elements of different approaches might be combined so that the whole can be more, rather than less, than the sum of its parts. The way forward is likely to be incremental and cumulative, bottom-up as well as top down -- transcending a too neat, and ultimately unhelpful, bifurcation between civil society advocacy and technocratic rule-making.